Turning the Tide on Poverty: History, theoretical frameworks, and methods. Issue 3 (26th May 2016) - Dyk, Patricia Hyjer; Monroe, Pamela A.; Tyler-Mackey, Crystal; Welborn, Rachel; Worthy, Sheri Lokken
Abstract: Desiring to enhance understanding of the key elements that promote community-based democratic engagement and spur people to engage in the vitality of their communities, in 2008 the Turning the Tide on Poverty project launched in six southern US states. Inspired by the successes of the Horizons project in the northwestern US, Tide was a collaborative effort led by the Southern Rural Development Center with partners that included the Kettering Foundation, Everyday Democracy, the Farm Foundation, and land-grant universities. Researchers and Cooperative Extension personnel from southern universities developed a strategy to involve residents in the process of addressing challenges in their impoverished communities. The purpose of this article is to present a brief history and overview of the project, to locate the project within theoretical frameworks, and to discuss the methods used for data collection and analysis. In so doing, we provide a context for the scholarly examination of Tide that follows in this special collection of Community Development .